2013
DOI: 10.1371/journal.pone.0059863
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Human Cytomegalovirus Transmission Correlates with Delayed Maternal Antibodies to gH/gL/pUL128-130-131 Complex during Primary Infection

Abstract: Primary human cytomegalovirus (HCMV) infections during pregnancy are associated with a high risk of virus transmission to the fetus. To identify correlates of intrauterine HCMV transmission, serial serum samples from HCMV transmitter and non-transmitter pregnant women with primary HCMV infection were analyzed for the presence of neutralizing antibodies against different glycoproteins and glycoprotein complexes, which are known to mediate entry into distinct types of host cells. Neutralizing activity was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
196
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 178 publications
(209 citation statements)
references
References 42 publications
(57 reference statements)
9
196
4
Order By: Relevance
“…Previous data showed that neutralizing antibodies, as measured in endothelial or epithelial cells with the use of the VR1814 CMV prototype, are directed primarily against the pentameric gH/gL/pUL128L complex 17,18 and represent the major neutralizing component of human serum and commercial hyperimmune globulin. 19,20 As confirmed in this study, these neutralizing antibodies are produced and peak very early after the onset of primary infection, without a clear difference between mothers who transmit the virus and mothers who do not. 12,21 On the other hand, neutralizing antibodies against AD169 are slower to develop, 12,21,22 and in our study, administration of hyperimmune globulin did not significantly modify their levels.…”
Section: Discussionsupporting
confidence: 66%
“…Previous data showed that neutralizing antibodies, as measured in endothelial or epithelial cells with the use of the VR1814 CMV prototype, are directed primarily against the pentameric gH/gL/pUL128L complex 17,18 and represent the major neutralizing component of human serum and commercial hyperimmune globulin. 19,20 As confirmed in this study, these neutralizing antibodies are produced and peak very early after the onset of primary infection, without a clear difference between mothers who transmit the virus and mothers who do not. 12,21 On the other hand, neutralizing antibodies against AD169 are slower to develop, 12,21,22 and in our study, administration of hyperimmune globulin did not significantly modify their levels.…”
Section: Discussionsupporting
confidence: 66%
“…Total IgG binding responses to either a fibroblast or epithelial-tropic CMV strain did not predict transmission risk. Similar to previous findings in primary maternal CMV infection, the maternal fibroblast neutralizing response also did not predict cCMV transmission [33]. Last, we assessed the binding specificity of maternal IgG antibodies to the CMV glycoproteins gH/gL, gH/gL/gO, and gB and defined neutralizing epitopes of CMV gB and gH.…”
Section: Discussionsupporting
confidence: 67%
“…We report no association between maternal IgG avidity and risk of CMV transmission among HIV-infected women, yet all had high IgG avidity (RAI range, 0.63-1.00), as expected in a cohort of women with chronic CMV infection. More recently, work by Lilleri et al showed that CMV-nontransmitting women with primary infection had a more rapid appearance of IgG against gH/gL and the pentamer than CMV-transmitting women [33]. In our study, both CMV-transmitting and nontransmitting women had preexisting CMV-specific IgG responses, yet we were able to determine whether the magnitude of pentamerspecific IgG was associated with transmission risk.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In the last few years, significant progress has been made in the diagnosis of human cytomegalovirus (HCMV) infections both for viral DNA quantification by real-time PCR (recently standardized with reference to the WHO International Standard; Furione et al, 2012), and antibody response determination to the HCMV envelope glycoprotein complexes gH/gL/pUL128L (the pentameric complex), gH/gL and gB as well as neutralizing antibodies (Genini et al, 2011;Lilleri et al, 2012Lilleri et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%